Identification and Characterization of Proteins in Association with Ribosomal Protein, eL27 in Nasopharyngeal Carcinoma Cells - Yew, Keh Li (Universiti Malaysia Sarawak (UNIMAS), 2019)
Ribosomal proteins (RPs) were only believed to involve in ribosome biogenesis and protein synthesis but there are increasing evidences to show the potential extraribosomal functions of ribosomal proteins. Ribosomal proteins are involved in regulation of cellular cell growth and differentiation as many studies have linked cancers to the differential expression of RPs. The ribosomal protein, eL27 has shown significant differential expression in cell lines derived from nasopharyngeal carcinoma (NPC) as compared to normal nasopharyngeal epithelium at both transcript and protein level. However, the protein-interacting partners of RPeL27 in NPC remains largely unknown. Hence, in this study we identified and characterized the proteins affected by RPeL27-knockdown in NPC via siRNA knockdown, 2-Dimensional Gel Electrophoresis (2D GE), liquid chromatography mass spectrometry (LCMS) and bioinformatics analysis. We successfully identified 15 differentially expressed proteins in RPeL27-knockdown HK1 cells and all the 15 proteins are cancer-related, often dysregulated in various diseases and take part in significant biological processes responsible for proper cell growth and proliferation. Therefore, the overexpression of RPeL27 could be responsible for NPC development and progression through association with 15 proteins identified either directly or indirectly. We predicted the possible protein interactions between RPeL27 and the 15 proteins identified via in silico approach. Our findings reinforce the potential role of ribosomal protein L27 in the carcinogenesis of NPC and provided the possible protein interactions between RPeL27 and 15 proteins.